2008
DOI: 10.1016/j.jda.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An efficient representation of Benes networks and its applications

Abstract: The most popular bounded-degree derivative network of the hypercube is the butterfly network. The Benes network consists of back-to-back butterflies. There exist a number of topological representations that are used to describe butterfly-like architectures. We identify a new topological representation of butterfly and Benes networks.The minimum metric dimension problem is to find a minimum set of vertices of a graph G(V , E) such that for every pair of vertices u and v of G, there exists a vertex w with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 1 publication
0
43
0
2
Order By: Relevance
“…Imran et al studied various degree based topological indices for various networks like silicates, hexagonal, honeycomb and oxide in [14]. For further study of topological indices of various graph families see, [2,9,10,12,13,15,18,[22][23][24][25]29,31,37]. …”
Section: Resultsmentioning
confidence: 99%
“…Imran et al studied various degree based topological indices for various networks like silicates, hexagonal, honeycomb and oxide in [14]. For further study of topological indices of various graph families see, [2,9,10,12,13,15,18,[22][23][24][25]29,31,37]. …”
Section: Resultsmentioning
confidence: 99%
“…The basic idea of this proof is due to Khuller et al [7] and Manuel et al [8]. Question: Given a graph GðV; EÞ and an integer k, does there exist a set C of k vertices such that G admits a resolvingpower dominating set?…”
Section: Complexity Results Of Resolving-power Domination Problemmentioning
confidence: 99%
“…It has been proved that the metric dimension problem is NP-hard [2] for general graphs. Manuel et al [9] have shown that the problem remains NP-complete for bipartite graphs. There are many applications of resolving sets to problems of network discovery and verification [1], pattern recognition, image processing and robot navigation [2], geometrical routing protocols [10], connected joins in graphs [11] and coin weighing problems [12].…”
Section: An Overview Of the Papermentioning
confidence: 99%
“…There are many applications of resolving sets to problems of network discovery and verification [1], pattern recognition, image processing and robot navigation [2], geometrical routing protocols [10], connected joins in graphs [11] and coin weighing problems [12]. This problem has been studied for trees, multi-dimensional grids [2], Petersen graphs [13], torus networks [14], Benes networks [9], honeycomb networks [15], enhanced hypercubes [16] and Illiac networks [17].…”
Section: An Overview Of the Papermentioning
confidence: 99%